2013
DOI: 10.1002/ange.201300574
|View full text |Cite
|
Sign up to set email alerts
|

Direct Synthesis of Pyrroles by Dehydrogenative Coupling of β‐Aminoalcohols with Secondary Alcohols Catalyzed by Ruthenium Pincer Complexes

Abstract: Angew. Chem., Int. Ed. 52 (2013) 14, 4012-4015, http://dx.doi.org/10.1002/anie.201300574 ; Dep. Org. Chem., Weizmann Inst. Sci., Rehovot 76100, Israel; Eng.) -Roessler 35-105

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(21 citation statements)
references
References 95 publications
0
20
0
1
Order By: Relevance
“…Interestingly, the groups of Kempe and Milstein published the iridium-and ruthenium-catalyzed synthesis of pyrroles and pyridines from secondary alcohols and 1,2-or 1,3-aminoalcohols, respectively. [14] At the same time, our research group reported the ruthenium-catalyzed three-component synthesis of pyrroles by using benzylic ketones, vicinal diols, and amines. [15] Based on this work, we considered the synthesis of indoles by using a similar dehydrogenative methodology, starting from anilines and epoxides.…”
mentioning
confidence: 99%
“…Interestingly, the groups of Kempe and Milstein published the iridium-and ruthenium-catalyzed synthesis of pyrroles and pyridines from secondary alcohols and 1,2-or 1,3-aminoalcohols, respectively. [14] At the same time, our research group reported the ruthenium-catalyzed three-component synthesis of pyrroles by using benzylic ketones, vicinal diols, and amines. [15] Based on this work, we considered the synthesis of indoles by using a similar dehydrogenative methodology, starting from anilines and epoxides.…”
mentioning
confidence: 99%
“…[5,6] Thus, the direct assembly of pyrroles from basic chemicals remains an important research objective. [7] Isocyanides [8] and alkynes [9] are two classes of commercially available and versatile starting materials. The atom-economic nature of the reaction makes the cycloaddition of these substrates an ideal route to oligosubstituted pyrroles (Scheme 1).…”
mentioning
confidence: 99%
“…Eine solche Synthese könnte eine deutlich schnellere Akzeptanz zur Folge haben, wenn sie den Zugang zu vielfältig funktionalisierten Pyridinen, die unter Verwendung bekannter Methoden schwer herzustellen sind, ermöglicht. Kürzlich entwickelten die Gruppen von Beller5a und Milstein6a sowie unsere Gruppe6b nachhaltige katalytische Pyrrolsynthesen, die auf dehydrierenden Kondensationsschritten beruhen (Schema , oben).…”
Section: Methodsunclassified